Analisis Panjang Gelombang Laser Monokromatik Melaui Pola Interferensi Cahaya Dari Kisi Difraksi Transmisi - Nurul Fatihah; Fatah Ari Kusuma Wardhana; Giovanni Krisostomos Ory Putra; Rida Siti Nur’aini Mahmudah (Jurnal Teori dan Aplikasi Fisika, 2024)
This study aimed to prove the concept of diffraction by determining the wavelength of green (532 ± 10) nm and purple (405 ± 10) nm laser pointers using transmission diffraction gratings of light interference patterns. The wavelength measurement results are then compared with the wavelength indicated on the laser. In this study, the distance between the grid and the screen (L) was varied by 100 cm, 75 cm, and 50 cm while the distance between the gaps (d) was varied by 100 lines/mm, 300 lines/mm, and 600 lines/mm. The method used in this study is an experimental method using a transmission diffraction grid and the interference results are displayed on the screen. The results showed data on brightspot distances of order n-1, 2, and 3 from the center of the pattern with variations in laser green and purple, variations in screen distance with grids (L) 100 cm, 75 cm, and 100 cm, and variations in gap width (d) 100 lines/mm, 300 lines/mm, and 600 lines/mm. The data is then analyzed using the bright-pattern constructive interference equation to determine the wavelength. Based on wavelength measurement data, at the same lattice distance with the screen (L) and lattice width (d), the green laser has a brighter distance that is farther apart than the purple laser. The conclusion of this study is that when the gap width is smaller, the distance between the brights will be farther apart or the x value is larger, the results of measuring the wavelength are appropriate on the green laser (532 ± 11) nm, and close to the purple laser (412 ± 23).   Keywords: Wavelength, Laser, Transmission grating, Diffraction, Interference.